MiR‐92a enhances recombinant protein productivity in CHO cells by increasing intracellular cholesterol levels. Issue 4 (15th March 2017) - Loh, Wan Ping; Yang, Yuansheng; Lam, Kong Peng
Abstract: MicroRNAs (miRNAs) have emerged as promising targets for engineering of CHO cell factories to enhance recombinant protein productivity. Manipulation of miRNA levels in CHO cells have been shown to improve product yield by increasing proliferation and specific productivity (qP), resisting apoptosis and enhancing oxidative metabolism. The authors previously demonstrated that over‐expressing miR‐92a results in increases in qP and titer of CHO‐IgG cells. However, the mechanisms by which miR‐92a enhances qP in CHO cells are still uninvestigated. Here, the authors report the identification of insig1, a regulator of cholesterol biosynthesis, as a target of miR‐92a using computational prediction. Both transient and stable over‐expression of miR‐92a decreased the expression levels of insig1 . Insig1 was further validated as a target of miR‐92a using 3' UTR reporter assay. Intracellular cholesterol concentration of two high‐producing miR‐92a clones were significantly increased by ≈30% compared to the blank‐transfected pool. Relative Golgi surface area was also found to be 18–26% higher in these clones. Our findings suggest that miR‐92a may affect cholesterol metabolism by repressing insig1, resulting in raised intracellular cholesterol levels and Golgi volume and hence enhanced protein secretion. Abstract : Over‐expression of miR‐92a was previously found to increase productivity of CHO‐Ig cells. The authors identified insig1 as a target of miR‐92a. Repression of insig1 by miR‐92a over‐expression resulted in increased cholesterol levels and Golgi volume, which could have contributed to the enhancement in protein productivity. This work elucidated a novel pathway via which miR‐92a could mediate productivity in CHO cells .